PEMBUATAN KOLAM TERASERING UNTUK BUDIDAYA IKAN DI RW 23 DESA CILAME KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT - Marlina, Lusi; Rohmayani, Dini; Yuliana, Ade; Listiana, Reni; Iskandar, Rachmat (ASOSIASI IDEBAHASA KEPRI, 2024)
A community service team from TEDC Bandung Polytechnic conducted a community service activity in Cilame Village, Bandung Barat Regency. The activity was the construction of terraced ponds for fish farming. This activity aims to help improve the economy of Cilame Village residents with low incomes. The activity began with the formation of a community service team consisting of 13 people. The team then conducted a field survey to determine the location and theme of the community service. After that, the team made a letter of request to the Head of Rukun Warga 23, Cilame Village. The construction of the terraced pond was carried out at one of the residents' houses which had unused land in the front yard of their house. The pond is 2 meters x 1 meter x 0.5 meters in size. After the pond was completed, the community service team provided catfish and tilapia fry to the resident. The activity went smoothly and was completed on time. On April 12, 2021, the community service team handed over the pond to the residents of Cilame Village.